Acoustic and Kinematic Correlates of Heterosyllabicity in Different Phonological Contexts. (September 2022) - Celata, Chiara; Meluzzi, Chiara; Bertini, Chiara
We investigate the temporal and kinematic properties of consonant gemination and heterosyllabic clusters as opposed to singletons and tautosyllabic clusters in Italian. The data show that the singleton versus geminate contrast is conveyed by specific kinematic properties in addition to systematic durational differences in both the consonantal and vocalic intervals; by contrast, tautosyllabic and heterosyllabic clusters differ significantly for the duration of the consonantal interval but do not vary systematically with respect to the vocalic interval and cannot be consistently differentiated at the kinematic level. We conclude that systematic variations in acoustic vowel duration and the kinematics of tongue tip gestures represent the phonetic correlates of the segmental phonological contrast between short and long consonants, rather than of syllable structure. Data are only partly consistent with the predictions of both moraic and gesture-based models of the syllable about the effects of syllable structure on speech production dynamics and call for a more gradient view of syllabification.